ON THE GENESIS OF TRAPP MAGMATISM OF THE SIBERIAN PLATFORM - Zorin Yu.A.; Vladimirov B.M. (My University, 1989)
Mathematical modelling of thermal thickening of the lithosphere with time indicates that the thickness of the lithosphere beneath the Siberian platform in the late Permian and Triassic, when intensive trapp magmatism occurred, differed insignificantly from the present thickness. Therefore, we infer that the source of trapp magma (mainly tholeiitic) was located at the depth of 180-200 km. We conclude that this tholeiitic magma was generated by complete melting of large eclogitic lenses enclosed in the lower lithosphere of the ancient craton.
Keywords: Permian; Triassic; Палеозой::Пермская; Mesozoic::Triassic; Paleozoic::Permian; Мезозой::Триасовая